Manipulation of indoleamine 2,3-dioxygenase (IDO) for clinical transplantation: promises and challenges - Quan, J; Tan, P; MacDonald, A; Friend, P (2008)
Background: Since the discovery that indoleamine 2,3-dioxygenase (IDO) is a modulator for maintenance of fetomaternal immuno-privilege state, it has been implicated in tumour tolerance, autoimmune diseases and asthma. IDO is an IFN-γ-inducible, intracellular enzyme that catalyzes the initial and rate-limiting step in the degradation of tryptophan. It has been suggested that IDO can regulate the immune system either through deprivation of tryptophan that is essential for T cell proliferation or via cytotoxic effects of kynurenine pathway metabolites on T cell survival. Methods: The sources of information used were obtained through Pubmed/ medline. Results/conclusion: While IDO emerges as a regulator of immunity, its role in controlling allo-response is unfolding. IDO can control T cell responses to allo-antigens and induce generation of allo-specific regulatory T cells. Exploiting IDO as a modulator of transplant rejection, many groups have manipulated its activity to prolong allograft survival in transplantation models. Despite the initial promise, its application to clinical transplantation may be limited. We therefore examine the potentials and limitations associated with clinical translation of IDO into a therapeutic. © 2008 Informa UK Ltd.